Factors modulating the impact of the COVID-19 pandemic on posttraumatic stress symptomatology of the Spanish healthcare workers: A cohort study. - Beatriz Arregui-Gallego; María Isabel Orts-Cortés; María Teresa Moreno-Casbas; Eva Abad-Corpa; Rafaela Camacho-Bejarano; Mª Ángeles Cidoncha-Moreno; Isabel Feria-Raposo; Javier Iruzubieta-Barragán; Montserrat Carmona; Estíbaliz Cristóbal-Domínguez; Leticia Bernués-Caudillo; Elvira Casado-Ramírez; et al. (PLoS ONE)
Introduction The COVID-19 pandemic generated a global health crisis that significantly impacted healthcare systems and professionals. Healthcare workers were exposed to high levels of psychological distress, including posttraumatic stress symptomatology (PTSS). Aim Analyse the evolution of PTSS among Spanish healthcare workers during the COVID-19 pandemic, and to identify associated factors. Method A multicenter prospective cohort study with a 12-month follow-up was conducted. PTSS was the primary outcome. Secondary variables included sociodemographic, occupational, psychological, and coping-related factors. Statistical analyses comprised bivariate comparisons and multivariate modelling, such as generalized linear models and linear mixed models. Results Of the 428 participants, 180 completed the 12-month follow-up. At baseline, changes in work posts, negative family-work relations, avoidant coping, burnout symptoms, and emotional intelligence were associated with PTSS levels. Linear mixed models showed a significant decrease in PTSS over the 12-month period, regardless of gender, age, household type, occupational role, contract type, job title, level of care or type of service (p < 0.001). The generalised linear model explained 25.5% of the variance in PTSS levels at baseline, highlighting the role of psychological and coping factors over sociodemographic or occupational characteristics. Conclusions This study highlights the need for early identification and intervention focused on psychological and coping mechanisms. Promoting emotional regulation, reducing burnout, and addressing maladaptive coping may help mitigate long-term psychological effects among healthcare workers during public health crises.